The scarcity heuristic impacts reward processing within the medial-frontal cortex. Issue 7 (4th May 2016) - Williams, Chad C.; Saffer, Boaz Y.; McCulloch, Robert B.; Krigolson, Olave E.
Abstract : Objects that are rare are often perceived to be inherently more valuable than objects that are abundant – a bias brought about in part by the scarcity heuristic. In the present study, we sought to test whether perception of rarity impacted reward evaluation within the human medial-frontal cortex. Here, participants played a gambling game in which they flipped rare and abundant 'cards' on a computer screen to win financial rewards while electroencephalographic data were recorded. Unbeknownst to participants, reward outcome and frequency was random and equivalent for both rare and abundant cards; thus, only a perception of scarcity was true. Analysis of the electroencephalographic data indicated that the P300 component of the event-related brain potential differed in amplitude for wins and losses following the selection of rare cards, but not following the selection of abundant cards. Importantly, then, we found that the perception of card rarity impacted reward processing even though reward feedback was independent of and subsequent to card selection. Our data indicate a top-down influence of the scarcity heuristic on reward evaluation, and specifically the processing of reward magnitude, within the human medial-frontal cortex.